The Implication of Unregulated Cryptocurrency Business on the Financial Industry in Uganda (a Case on Consumer Protection) - Noble Nomwesigwa (Uganda Christian University, 2025)
This thesis presents the effects of non-regulation of cryptocurrencies in Uganda. Cryptocurrencies are a form of digital or virtual currency generated, exchanged and distributed exclusively online. They have been an issue with want of regulation since 2017 as the National Bank has time and time again released circulars informing the population not to partake in the purchase or even trading of these currencies. Recently, the Central bank restricted all its licenses from cashing out proceeds from the crypto currency business, which sparked legal action and a deeper question into why instead of regulating the sphere, the Central bank and other concerned parties (parliament) do not draft legislation regulating the sphere. In this thesis, we shall explore the different regulatory measures that have been undertaken in other jurisdictions to ensure that the rights of the users of cryptocurrencies are protected from the uncertainties that arise as a result of non-regulation of the cryptocurrencies.
THESIS